Spanish Version of the Plymouth Sensory Imagery Questionnaire - Pérez-Fabello, María José; Campos, Alfredo (Frontiers in Psychology, 2020)
Objective: The current interest in mental imagery in fields such as sport and physical training, health, education, underscore the need for designing general measures of imagery vividness that include different sensorial modalities such as the Plymouth Sensory Imagery Questionnaire (Psi-Q; Andrade, May, Deeprose, Baugh, & Ganis, 2014). The Psi-Q measures imagery vividness in seven sensorial modalities with a factorial structure of seven factors corresponding to the sensorial modalities, and has good internal consistency. The aim of the present study was to translate the Psi-Q into Spanish and to assess its psychometric properties. Method: The questionnaire was back-translated, and administered to 394 fine arts undergraduates. Moreover, this test was compared to other questionnaires measuring different types de imagery. Results: A confirmatory factor analysis found that the Psi-Q had seven factors (vision, sound, smell, taste, touch, bodily sensation, and emotional feeling) with results similar to the original test. Values suggested a better fit for the model of the short version. The internal consistency values were .93 for the long and .89 for the short test. The Psi-Q subscales correlated significantly (p < .01) with the total of the Betts’ QMI subscales, and the VVIQ, with the highest significance observed between the Psi-Q Touch and Betts’ QMI Cutaneous (r = -.57), and between the Psi-Q Olfactory and Betts’ QMI Smell (r = -.56). Owing to its novelty, the high correlation and significance (p < .01) between Psi-Q Vision and the OSIVQ Object (r = .36) is worth noting. Conclusions: The Spanish version of the Psi-Q was an adequate measure for evaluating different sensorial modalities of imagery vividness, and exhibited similar psychometric properties to those of the original version. The growing interest in mental imagery in different fields of application justifies the need for adapting the Psi-Q for the Spanish speaking population. This questionnaire is a valuable tool for the understanding of imagery as a psychological process, and as a variable influencing other processes.